Perdas de familiares e a vivência do luto na trajetória da formação graduada de estudantes de terapia ocupacional - Santos, Gabriela Lourenço dos (Universidade Federal de São Carlos, 2026)
This study aimed to understand the experiences of loss and grief among undergraduate Occupational Therapy students and how these experiences affect their educational process. This is a descriptive multiple-case study with a qualitative approach. The participants were final-year Occupational Therapy students at the Federal University of São Carlos who had experienced the loss of a family member within the previous five years. Data were collected through individual interviews guided by a semi-structured interview protocol developed based on thanatology literature. The data were summarized on a case-by-case basis and analyzed using Bardin's content analysis. Four female undergraduate students participated in the study. The results showed that the losses were related to the death of elderly family members, and that the grieving process was influenced by the quality of the bond with the deceased and the circumstances surrounding the death. The findings revealed unique and multidimensional repercussions of grief, with social support networks emerging as one of the main resources for coping. The study also identified both the impact of grief on professional education and the influence of academic training on the grieving experience. It is concluded that experiences of loss and grief permeate the educational process in health professions, influencing the development of perspectives on care.
Loss of family members and the experience of bereavement during the undergraduate training of occupational therapy students
Keywords: Morte; Luto; Atividades de formação; Tanatologia; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar